PROBLEMS OF HERNIOPLASTY OF DIAPHRAGMATIC HERNIAS - Shukurov Mamed Bahodirovich; Yarikulov Shuxrat Shokirovich (The latest news and research in education, 2025)
The purpose of the study: to analyze the surgical treatment of large and giant hernias of the esophageal orifice of the diaphragm (GPOD). Materials and methods a review of the medical literature on the latest research on the surgical treatment of HIP has been conducted, the main problems have been identified, and the results of their own experience using various types of plastic surgery have been shown.